THE MORPHOLOGY OF A MESSINIAN VALLEY AND ITS HINTERLAND (VENTIMIGLIA, NW ITALY): A MIOCENE TO PLIOCENE RECONSTRUCTION - Foeken J.P.T.; Bertotti G.; Dunai T.J. (My University, 2006)
Along the Ligurian coast (NW Italy), Alpine-folded and slightly metamorphosed rocks experienced fluvial to marine erosion prior to and during the base level fall associated with the Messinian salinity crisis. Following the subsequent sea-level rise at the onset of the Pliocene, valleys incised along the coastal margins during the Messinian salinity crisis were partly filled with Pliocene marine and continental deposits. One such valley-infill system is exposed near Ventimiglia (NW Italy). Using geological cross-sections and geomorphological analysis we have constrained its shape and dimensions, as well as the morphology of its hinterland. The Messinian valley was very open, ~10 km wide and probably 500 m deep. The basal unconformity between the Pliocene sediments and the underlying substratum is characterized by a smooth surface that has on either side of the palaeo-valley a dip between 2 and 10°. The basal unconformity in the southernmost part of the palaeo-valley roughly coincides with present-day sea level. The hinterland of the middle Pliocene sea was characterized by kilometres-wide valleys surrounded by mountains with a relief gentler than at present. The shapes and dimensions of the Messinian Ventimiglia valley and the relief during Pliocene times are different from those derived from comparable structures in SE France and NW Italy. We interpret this as being due to the exhumation history that the Ventimiglia region, different from the surrounding areas, experienced over the last few million years. Copyright © 2006 John Wiley & Sons, Ltd.
Keywords: DELTA; LIGURIAN ALPS; MESSINIAN VALLEY; MORPHOLOGY; TECTONIC EVOLUTION; Pliocene; Messinian; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene::Messinian; Кайнозой::Неоген::Миоцен::Мессинский